The Performance of the Fire Service Office of Central Bengkulu Regency in Dealing with Fire Hazards - Risondi Risondi; Evi Lorita; Antonio Imanda; Marida Sari Ningsih (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the performance of Central Bengkulu Regency Fire Department in dealing with fire hazards. Data collection techniques were carried out by means of in-depth interviews, observation and documentation. After the research results were obtained, they were analyzed by means of data reduction, data presentation and conclusion drawing. There were 6 informants in this study consisting of 3 key informants and 3 main informants. This study used the theory of Lazer 1977 in Bintoro and Daryanto (2017:153). The Technician component, in accepting prospective employees at the Fire Department, must have requirements such as an equivalent high school diploma, physically and mentally healthy, male height 165 cm and female 160 cm and have special skills. The training and seminars conducted by the firefighters are limited in nature, not all officers receive special training, only firefighters who are close to the leadership can attend training and seminars. Conceptual ability, the way the leader overcomes problems that occur in the field by using a personal approach to firefighters or employees to overcome the problem of fire hazards. The leadership takes a personal approach to each officer and the existing units or posts so that they can give direct responsibility to Danton in giving orders to existing officers. Interpersonal Relations Ability, the leaders only receive reports from Danton about information on fires that have occurred in the community. The leaders rarely go directly to the scene of a fire incident. The community was dissatisfied with the performance of the firefighters in extinguishing the fire at the fire site due to the delay in the fleet of cars arriving at the location to extinguish the fire.